PERANCANGAN VISUALISASI JURNAL “TALENTIFY” SEBAGAI MEDIA IDENTIFIKASI MINAT DIRI REMAJA - Zalshabila Audrea Putri Arine; Shienny Megawati Sutanto (Jurnal Vicidi, 2021)
Talentify is an activity book that is used to help highschool teenager to explore their interests in order to prevent the phenomenon of misdirecting college major. From the first market research on extreme users and expert users, a visual problem was discovered where Talentify book was considered too stodgy to read and fill, this was due to the dominance of text's composition, also the minimum frequent of visual elements such as illustrations and symbols. Therefore, the purpose of this design is to overcome the visual problems of Talentify product as described above so that the book appearance looks more fun and challenging to fill. This design uses secondary data collection methods. The secondary data is the result of literature studies through related journals and books such as visual design, activity books, reflective journals, and interactive content. These summaries will be considered as the basic knowledge to redesign the appearance of the book. The result of this design is the visual element and the book graphic design itself with more "fun" concept which associates with the brand identity, also layouts and illustrations which more organized according to visual hierarchy that does not causing a stodgy feeling when the users fill and read the book. Keywords: Activity Book, Interactive Journal, Self-Interest.